2017
DOI: 10.1080/00015385.2017.1314134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of losartan as add-on therapy to prevent aortic growth and ventricular dysfunction in patients with Marfan syndrome: a randomized, double-blind clinical trial

Abstract: Losartan on top of beta-blocker therapy has no additional effect on aortic growth or on cardiac function in patients with MFS. Our results are underpowered but are in line with the result from other groups. In order to have a better insight on whether a group of patients could benefit more from losartan therapy, the outcome of an on-going meta-analysis should be awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…The final analysis included seven clinical trials [15, 7, 8], with a total of 1352 patients and average weighted follow-up of 37.8 months (Fig. 1; Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final analysis included seven clinical trials [15, 7, 8], with a total of 1352 patients and average weighted follow-up of 37.8 months (Fig. 1; Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed a lower degree of heterogeneity by excluding the studies by Lacro et al [2] and Chiu et al [4] (MD = −0.07; 95% CI −0.08 to −0.05; p < 0.001; I 2 = 24%). Subgroup analysis according to the control group showed no significant subgroup interaction when comparing losartan with beta-blockers [1, 2, 4, 7] versus with standard therapy [3, 5, 8] ( p interaction = 0.27). A change in the diameter of the ascending aorta was reported in six studies, and analysis showed no significant difference between the losartan and control groups (MD = −0.02; 95% CI −0.14 to −0.11; p = 0.78; I 2 = 98%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiu et al [ 72 ] reported that addition of Losartan to beta-blockers in a young patient group did result in reduced rate of aortic dilatation, although the annual rate of aortic dilatation amongst those receiving only beta-blockers was greater than that reported in any other clinical study. In contrast, neither the Ghent [ 73 ] nor the Vancouver [ 74 ] studies observed any apparent benefit from Losartan treatment, with the latter study conducted in a similar age group to the Taiwan study.…”
Section: Angiotensin II and Aortic Aneurysm In Marfan Syndrome - Clinmentioning
confidence: 93%
“…Experimental models of Marfan syndrome suggest that angiotensin-II type 1 receptor blockers (ARBs) can alter biological pathways, including excessive TGF-β signalling, that might contribute to the pathogenesis of aortic complications,5, 6, 7, 8 a finding that is supported by observational data in clinical studies 9 . Randomised trials in Marfan syndrome have compared the effects of the ARB losartan with either β blockers or control (where standard medical therapy could include β blockers) on aortic dilatation10, 11, 12, 13, 14, 15 without clear evidence of benefit. Other ARBs, such as irbesartan, might have greater bioavailability and a longer half-life than losartan with more potent antihypertensive effects.…”
Section: Introductionmentioning
confidence: 99%